Confirmation of the reported association of clonal chromosomal mosaicism with an increased risk of incident hematologic cancer. - Ursula M Schick; Andrew McDavid; Paul K Crane; Noah Weston; Kelly Ehrlich; Katherine M Newton; Robert Wallace; Ebony Bookman; Tabitha Harrison; Aaron Aragaki; David R Crosslin; Sophia S Wang; et al. (PLoS ONE)
Chromosomal abnormalities provide clinical utility in the diagnosis and treatment of hematologic malignancies, and may be predictive of malignant transformation in individuals without apparent clinical presentation of a hematologic cancer. In an effort to confirm previous reports of an association between clonal mosaicism and incident hematologic cancer, we applied the anomDetectBAF algorithm to call chromosomal anomalies in genotype data from previously conducted Genome Wide Association Studies (GWAS). The genotypes were initially collected from DNA derived from peripheral blood of 12,176 participants in the Group Health electronic Medical Records and Genomics study (eMERGE) and the Women's Health Initiative (WHI). We detected clonal mosaicism in 169 individuals (1.4%) and large clonal mosaic events (>2 mb) in 117 (1.0%) individuals. Though only 9.5% of clonal mosaic carriers had an incident diagnosis of hematologic cancer (multiple myeloma, myelodysplastic syndrome, lymphoma, or leukemia), the carriers had a 5.5-fold increased risk (95% CI: 3.3-9.3; p-value = 7.5×10(-11)) of developing these cancers subsequently. Carriers of large mosaic anomalies showed particularly pronounced risk of subsequent leukemia (HR = 19.2, 95% CI: 8.9-41.6; p-value = 7.3×10(-14)). Thus we independently confirm the association between detectable clonal mosaicism and hematologic cancer found previously in two recent publications.